Analisis Kesalahan Menulis Bahasa Arab Dalam Pembelajaran Imla` - Anyes Lathifatul Insaniyah; Umi Yurika Nur Kumala (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2022)
Writing skill is one of four Arabic language skills. As for improving writing skills, it can be obtained by learning imla`. Imla` is an Arabic writing exercise, where the process is where the teacher reads a text or script and then the students write it down. This study aims to describe the forms of basic errors in writing Arabic for class and 1-E Ulya Madrasah Diniyah Al Amiriyyah students. This research is a type of qualitative research that is descriptive in processing the data and uses error analysis in its analysis. In this study, researchers used several methods in collecting data including the method of tests, observations, interviews, documentation. The forms of errors found in this study include errors in writing hamzah, hamzah qotho`, errors in subtracting letters, adding letters, errors in changing letters and writing ta`. The basic factors that encourage students are ignorance of the correct form of writing, less accustomed to writing Arabic script and the lack of ability in the fields of nahwu and shorof.